Incidence of otitic barotrauma during decompression chamber test in Indian armed forces between 2019 and 2022 - Avishek Sharma; G Harshavardhan; Karthikeyan Sankaran (Indian Journal of Aerospace Medicine, 2026)
Objectives: Combat free-fall (CFF) jumps are undertaken by special forces of the Armed Forces for the conduct of various operations. These jumps expose paratroopers to barometric changes, making them prone to various types of barotrauma. Indoctrination on middle ear pressure equalization techniques in the Decompression Chamber (DC) before the actual training helps the personnel to understand the physiological changes and thereby helps in reducing the probability of barotrauma. However, simulation of these barometric changes for training in DC also has the potential to cause injuries. Material and Methods: A retrospective analysis of cases of otitic barotrauma that occurred among the Indian Armed Forces personnel, who reported to the Institute of Aerospace Medicine between October 2019 and September 2022, was conducted. A total of 639 soldiers in the age group of 20–45 years volunteered for CFF training, out of which 609 were exposed to DC test. The test protocol included hypoxia indoctrination at simulated altitude of 25000 ft with an ascent and descent rate of 3,000 ft/min, after a successful Ear Clearance Run (ECR). Results: Over a period of 3 years, a total of 639 soldiers volunteered for CFF training. Out of that, 30 were declared unfit during initial clinical examination, otoscopic findings and ECR. Among the remaining 609 soldiers, a total of 40 suffered barotrauma. The incidece of barotraume was 6.51% in Army Paratroopers, 3.33% in Marcos and 8.40% in Garuds. Conclusion: This study brings out the incidence of Otitic barotrauma in Paratroopers of the Indian Army, Marcos of the Indian Navy and Garuds of the Indian Air Force. The study revealed an incidence of 6.56% as compared to 7.4% cited by the previous study conducted at the same institute in 2018.